Preliminary investigations of the risk of plant debris as a Pseudomonas syringae pv actinidiae inoculum source - Tyson, J.L.; Curtis, C.L.; Manning, M.A.; Dobson, S.J.; McKenna, C.E. (New Zealand Plant Protection, 2016)
In New Zealand the causal agent of kiwifruit canker Pseudomonas syringae pv actinidiae (Psa) can survive in overwintered kiwifruit plant debris on the orchard floor at least until spring This study used trap plates and trap plants to determine the importance of fallen leaves and winter prunings on the orchard floor as inoculum sources Trap plates were positioned 15 50 and 100 cm above the debris Psa was detected only when the plates were exposed during rain events and was found to be splashed upwards in small amounts from the debris during rain Leaf lesions developed only on the trap plants exposed during the first week of the 20week trial In this trial there is some evidence that plant debris is not a significant inoculum source and would not have posed a major risk for reinfection of any surrounding kiwifruit vines at the time of budburst in spring